A Specific and Sensitive Immuno-Terahertz Method to Detect Pathogenic Microorganisms - Xuehao Wang; Ye Tian; Fenli Liu; Lintao Huang; Fulai Zhang; Xupeng Fu; Yu Li; Qingliang Feng; Wen Zeng; Junli Liang; Donghao Cheng; Yadong Xu; et al. (Advanced Devices & Instrumentation)
Terahertz (THz)-based sensing technology shows promise for the rapid and efficient detection of unlabeled biomolecules and pathogens, attributed to their significant absorption in the THz range. However, its application has been limited by low sensitivity and specificity. Addressing this, we creatively constructed an advanced detection technique named immuno-THz technology, integrating monoclonal antibody (mAb)-based specific molecular recognition with THz sensing. Detection of a variety of pathogenic microorganisms was highly sensitive and specific in our proof-of-concept assay, achieving a limit of detection of 74.57 colony-forming units/ml for Escherichia coli O157:H7, 0.05495 μg/ml for HAdV-B55 Hexon protein, and 0.00479 μg/ml for Staphylococcal enterotoxin B in phosphate-buffered saline solution. The immuno-THz technique substantially enhances detection sensitivity, marking a 100-fold improvement over traditional THz spectroscopy methods, particularly in detecting E. coli O157:H7. The advanced sensitivity and specificity of the immuno-THz technique will offer an improved approach for the detection of pathogenic microorganisms, be applied in a wide range of applications, and impact on food safety and public health and national defense security.